Developing Sustainable Competitive Advantage: The Role of Dynamic Capability and Innovation Performance in Excelsa Coffee Bean Industry - Artika, Siti; Toiba, Hery; Andriani, Dwi Retno (The University of Lampung, 2024)
This study examines the influence of sensing ability, seizing ability, reconfiguring capability, and innovation performance on sustainable competitive advantage (SCA) of the Excelsa Coffee Bean Processing Industry in Bojonegoro. Data was collected through questionnaires that have been tested for validity and reliability. The data analysis uses Structural Equation Modeling (SEM) with SmartPLS software. The results show that these four variables have a positive and significant influence on SCA. Sensing ability plays a role in detecting market changes, while seizing ability allows companies to take advantage of existing opportunities. Reconfiguring capability helps companies adjust resources to stay competitive, and innovation performance is a key factor in creating new ideas that are relevant to the market. The study also found that innovation performance mediates the influence of sensing ability and seizing ability on SCA, making it a key catalyst in turning market potential into competitive advantage. This finding has important implications for the industry, namely the need to improve sensing, seizing, reconfiguring, and innovation performance. Stakeholders, such as local governments and supporting institutions, are also expected to play a role in helping the industry through policies that support this capacity building. Keywords: Performance innovation, Reconfiguring capabilities, Seizing ability, Sensing ability, Sustainable competitive advantage.